Nuclear factories for replication, transcription and repair - McManus, J; Hughes, T; Pombo, A; Jones, E; Iborra, F; Jackson, D; Cook, P (1995)
Recent experiments suggest that the active polymerases involved in replication, transcription and the repair of damage in DNA are concentrated in large structures - 'factories' - within eukaryotic nuclei. This has forced us to reevaluate how polymerases work. The traditional view involved enzymes that tracked along templates and this was sensible if the polymerases were small relative to the templates and if they acted alone. However, immobilization of many polymerases within one factory means that the templates must move instead. Then the position of a gene in three-dimensional space relative to a factory will dictate how easily replication, transcription and repair can occur.